Anna o ebook A novel. - Blake, Matthew (2024)
#1 International Bestseller GMA Buzz Pick • A Today Show Pick • A People Magazine Pick "A riveting, unsettling crime novel that will keep you turning pages well past your bedtime. Is Anna O a sleeping beauty or a sleeping killer? Matthew Blake's tension-filled thriller is as elusive and mysterious as sleep itself." — Nita Prose, #1 New York Times author of The Maid and The Mystery Guest Joining the ranks of Gillian Flynn, A. J. Finn, and Alex Michaelides, Matthew Blake delivers the thriller of the year: a dark, twisty, and shocking mystery about a young woman who commits a double murder while sleepwalking, and then never opens her eyes again. ANNA O WILL WAKE UP THE WORLD What if your nightmares weren't really nightmares at all? We spend an average of 33 years of our lives asleep. But what really happens, and what are we capable of, when we sleep? Anna Ogilvy was a budding twenty-five-year-old writer with a bright future. Then, one night, she stabbed two people to death with no apparent motive—and hasn't woken up since. Dubbed "Sleeping Beauty" by the tabloids, Anna's condition is a rare psychosomatic disorder known to neurologists as "resignation syndrome." Dr. Benedict Prince is a forensic psychologist and an expert in the field of sleep-related homicides. His methods are the last hope of solving the infamous "Anna O'"case and waking Anna up so she can stand trial. But he must be careful treating such a high-profile suspect—he's got career secrets and a complicated personal life of his own. As Anna shows the first signs of stirring, Benedict must determine what really happened and whether Anna should be held responsible for her crimes. Only Anna knows the truth about that night, but only Benedict knows how to discover it. And they're both in danger from what they find out.